Dichlorido[(1,2,3,3a,8b-η)-2,4-dimethylcyclopenta[b]indolyl)(η5-pentamethylcyclopentadienyl)zirconium(IV) - Michael G. Medvedev; Alexey N. Ryabov; Dmitry V. Uborsky; Dmitry S. Kononovich; Vyatcheslav V. Izmer; Alexander Z. Voskoboynikov (IUCrData, 2016)
In the structure of the title compound, [Zn(C13H12N)(C10H15)Cl2], the dihedral angle between the planes of rings coordinating to Zr is 51.6 (2)°. The Cl—Zr—Cl angle is 97.52 (4)°. The crystal structure is stabilized by H...Cl and C—H...π interactions.